Navigating Conflict Coverage on TikTok: Exploring Peace Journalism Practices Among Social Media Influencers - Stordy, Danielle (Université d'Ottawa | University of Ottawa, 2026)
This thesis examined how social media influencers (SMIs) covering international conflicts on TikTok embedded components of peace and violence within their video content. Using a qualitative-dominant method design, the Peace Journalism Model (PJM) was applied as the primary analytical coding framework and complemented with Critical Discourse Analysis for interpretive depth. Audience engagement metrics were also incorporated as a quantitative measure of content visibility and resonance. Findings indicate that SMIs incorporate elements aligned with Peace Journalism, often reflecting a justice-oriented framing that challenges dominant narratives and amplifies marginalised voices. At the same time, these coexist with violence-oriented narratives characterised by polarisation and moral absolutism. The findings are situated within broader debates on violence, identity, and peace-oriented communication through additional theoretical perspectives. The dataset presents ethical considerations and opportunities around influencer-driven communication within a social media environment shaped by algorithms, visibility, and a participatory culture. This study underscores the social and ethical responsibilities of both content creators and consumers. In addition, it offers a modernised application of the PJM to better capture the complexities of social media.
Keywords: TikTok; Social Media Influencers; Peace Journalism; Peace Communication; Media Ecology